2020
DOI: 10.3390/antiox9111061
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Obtained from Olea europaea By-Products and Their Use to Improve the Quality and Shelf Life of Meat and Meat Products—A Review

Abstract: Consumers are interested in consuming clean label foods. Replacing synthetic additives with natural alternatives (especially sources rich in polyphenols) is a valid solution to produce and also preserve foods, especially meat and meat products. Olea europaea leaves and olive pomace and wastewater contain polyphenols that can be explored in this context. In this review, we summarize the main aspects related to the phenolic composition, extraction conditions, antimicrobial potential, and antioxidant activity (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 120 publications
(183 reference statements)
1
25
0
Order By: Relevance
“…Dragsted (2008) found that the α‐amino groups of lysine underwent oxidation to form a carbonyl group, destroying the primary structure of the polypeptide chain and changing the hydrophobicity of the protein. The redox state is used to evaluate the formation of oxidation products, such as those from the lipids and proteins oxidation (carbonyl formation) (Munekata et al., 2020). The sulfhydryls in cysteine are easily oxidized to form disulfide bonds, cross‐linking proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Dragsted (2008) found that the α‐amino groups of lysine underwent oxidation to form a carbonyl group, destroying the primary structure of the polypeptide chain and changing the hydrophobicity of the protein. The redox state is used to evaluate the formation of oxidation products, such as those from the lipids and proteins oxidation (carbonyl formation) (Munekata et al., 2020). The sulfhydryls in cysteine are easily oxidized to form disulfide bonds, cross‐linking proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few decades these bioactive compounds have been used as feed supplements to enhance animal performance, health and welfare, and to manufacture functional foods of animal origin [3,10,[38][39][40]. Studies on applications for these by-products have attracted great interest not only from an environmental point of view but also from an economic and human health perspective, as producing functional foods containing natural extracts from the olive plant Olea europaea could prove to be an excellent food industry strategy for improving human health, well-being and immune function [6].…”
Section: Discussionmentioning
confidence: 99%
“…europa.eu/news/en/headlines/economy/20151201STO05603/circular-economy-definitionimportanceand-benefits, accessed on 18 May 2021) is particularly important for the agrofood sector as it aims to apply new techniques to recover valuable bioactive compounds from agri-food by-products to be used in animal nutrition [2][3][4][5]. Within the agri-food chain, the extra virgin olive oil production industry generates a wide variety of waste residues which have significant environmental impacts, such as olive vegetation waters, olive pomace and olive leaves [1,6]. Moreover, olive oil waste may negatively affect soil microbial populations, aqueous ecosystems and air medium due to its high phytotoxicity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxytyrosol (HTyr) and oleuropein (Ole) are two bioactive constituents of olive tree ( Olea europaea L., Figure 1 ) used as dietary supplements for their beneficial effects on human health or as food preservatives for their strong antioxidant activity [ 19 ]. HTyr is a low molecular weight phenol found mainly in olive fruits (16.6 mg/kg) [ 20 ]; Ole a secoiridoid can be found in both fruits (19.2 mg/kg) and leaves (26.47 mg/kg) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%